Dealing with Reduction Operations Using Transactional Memory - Gonzalez-Mesa, Miguel A.; Quislant, Ricardo; Gutierrez, Eladio; Plata, Oscar (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2013)
Reductions are common operations in many real-world applications that may be responsible for a significant part of the computing time. Modern compilers implement parallel reductions by combining privatization, atomic operations and/or locks. In this paper we analyze how to address reductions in the transactional memory (TM) model, which is flourishing together with the modern shared-memory multicore-based parallel architectures. With this purpose, this paper studies which support needs to be added to a TM system to deal with reductions as a special case of conflicting memory accesses.